Margaret Chase Smith Essay - Richards, David; Bernard, Chelsea; Walsh, Terrance; Sullivan, Stacy (Maine Policy Review, 2010)
Each year, the Margaret Chase Smith Library sponsors an essay contest for Maine high school seniors. The essay prompt for the 2009 contest was tied to a quote from Sen. Smith not to fear the inevitability of change. Essayists were asked to respond to the question, “What changes do you think the new administration will need to make, and we the people embrace, to reform American society?” Featured here are the three prize-winning essays.
Keywords: 2008 presidential election; U.S. politics; policy